2022
DOI: 10.3390/toxics10020052
|View full text |Cite|
|
Sign up to set email alerts
|

Copper and Zinc Levels in Commercial Marine Fish from Setiu, East Coast of Peninsular Malaysia

Abstract: Potentially toxic metals (PTMs) in edible marine fish have been widely reported from at least 15 different regions or countries in the literature. This evidently demonstrates the importance of monitoring the PTMs in fish fillets from a human health risk (HHR) point of view. This study aims to assess the HHR of Cu and Zn in 19 species of marine fish from popular marine fish loading sites at Setiu in Terengganu, on the east coast of Peninsular Malaysia, collected between August 2016 and February 2017. With overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 72 publications
4
11
0
Order By: Relevance
“…In 40 fish species, Cu concentrations varied from 0.06-16.9 mg/kg ww (0.72-82.3 mg/kg dw) (Figure 1; Table 1). This Cu range exceeds the 0.29-1.80 mg/kg ww; 1.50-7.83 mg/kg dw were reported for the 19 Setiu commercial fish species from the east coast of the Malaysian Peninsular [29]. The present Cu range (0.06-16.9 mg/kg ww) was significantly below the MPLs proposed by FAO [66] of 20-70 mg/kg ww, MAFF (20 mg/kg ww) [67], and MFR (30 mg/kg ww) [68].…”
Section: Comparison Of Cu Food Safety Recommendations and Reported Cu...mentioning
confidence: 53%
See 2 more Smart Citations
“…In 40 fish species, Cu concentrations varied from 0.06-16.9 mg/kg ww (0.72-82.3 mg/kg dw) (Figure 1; Table 1). This Cu range exceeds the 0.29-1.80 mg/kg ww; 1.50-7.83 mg/kg dw were reported for the 19 Setiu commercial fish species from the east coast of the Malaysian Peninsular [29]. The present Cu range (0.06-16.9 mg/kg ww) was significantly below the MPLs proposed by FAO [66] of 20-70 mg/kg ww, MAFF (20 mg/kg ww) [67], and MFR (30 mg/kg ww) [68].…”
Section: Comparison Of Cu Food Safety Recommendations and Reported Cu...mentioning
confidence: 53%
“…The common name, scientific name, exact purchase location, and purchase time were recorded in a table. The edible dorsal muscles of all fish samples were dissected for metal analysis as it is the primary storage site for Cu accumulation [29].…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Another report also demonstrated that for marine animals, imported high Cu accumulates in oysters (Crassostrea rivularis), can easily accumulate and transfer abnormal amounts of Cu to the upper trophic levels, and generates health risks for humans. 12 Yap et al 108 also concluded that Cu from marine fish is an important source for human health; the high amount of Cu intake from marine fish might cause health concerns to humans and animals, such as liver and kidney damage. In summary, a high concentration of Cu in water is great harm to all aquatic animals and plants.…”
Section: Copper and Wastewatermentioning
confidence: 99%
“…The published article [ 1 ] with the following sentence for Section 1, paragraph 5 of the MS: “Aegean Seas of Turkey [46,47]”. However, it must be noted that the Aegean Sea of Greece for citation 47 must be included.…”
Section: Text Correctionmentioning
confidence: 99%